Manajemen Peserta Didik Profesional dalam Praktik - Muhasim Muhasim (PALAPA, 2018)
Student management must first understand the management of both expert opinion and etymologically. In the general sense management as one of the system functions and utilization of elements of management within the organization. Another view views management as Science and Art, as a social process that views the functions of planning, organizing functions, mobilizing functions and oversight functions as a cycle. As a process that is to see the function of Planning is a decision in applying other management functions.The process of these management functions simultaneously regulates the relationships between functions and will serve as an overview of the flexibility of the planning function as an early organizing, moving and monitoring. In terms of management as described above, the management of learners can be defined as an effort to regulate the learners from the students enter the school until they graduate school. Student management focuses on the planning, arrangement, supervision and service of students in the classroom and beyond the classroom such as: recognition, enrollment, individual services such as the development of the overall skills, interests, needs until it matures in school. In prospective learners have a variety of expectations that must be realized when they have finished their education at the level of schooling. Prospective learners will succeed as required, if the management of learners is professionally managed. Professional teachers in the formation of attitudes as well as a set of competence learners that have knowledge, and skills. To examine the complexity of the method used in this paper, the descriptive method means to understand what the object of writing, to observe the various situations and social realities that exist in the community from various sources that can be trusted, writing, online media that match the object of writing. With this method found how important the management of professional learners in practice, in printing learners who have competencies as dictated by the learners themselves and educational institutions where learners are learning.